A history of Korean Christianity - Kim, Sebastian C. H. (Cambridge Univ. Press, 2015)
Machine generated contents note: 1. Introduction; 2. Believers, martyrs and missionaries, 1392-1876; 3. Evangelism, patriotism and revivalism, 1876-1910; 4. Oppression, resistance and millennial hope, 1910-45; 5. Liberation, service and divisions, 1945-61; 6. Growth, thought and struggle, 1961-88; 7. Missions, reconciliation and public life, 1988 to the present